Evolutionary Models of Convergent Margins Origin of Their Diversity - Itoh, Yasuto (IntechOpen, 2017)
This book deals with recent developments in evolutionary models for convergent margins. Reflecting transient modes for oceanic plate convergence, such boundaries are sites of varied tectonic processes, which provoke vigorous material recycling and frequent natural disasters such as massive earthquakes and catastrophic volcanism. Therefore, the origin of their diversity has long been one of the most significant themes in Earth science. The important scientific results obtained by prominent researchers who contributed chapters to this book pave the way for further in-depth studies on mobile belt frontiers, where harsh conditions hinder efforts to understand the Earth's spatiotemporal changes.